10. Summary of Some Aspects of Piano Interpretation in Schubert Sonatas, According to Musical Notation - Tudor Brîndușa (Sciendo, 2022)
In order to be able to reveal the constructive value and expressive force of Schubert's piano sonatas, one needs first of all a good edition that rends as precisely as possible the author's original text, as well the pianist's skill to bring score to life, therefore managing to transpose in his interpretation the composer's creative intentions, that are set by using the musical notation. We wish to highlight below some aspects of Schubert's musical notation regarding dynamics and sonority, sound emitting manners (legato and staccato) and pedalling.